2006
DOI: 10.1088/1367-2630/8/8/135
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-induced ferromagnetism in n-type ZnMnAlO and ZnCoAlO thin films at room temperature

Abstract: The realization of semiconductors that are ferromagnetic above room temperature will potentially lead to a new generation of spintronic devices with revolutionary electrical and optical properties. Transition temperatures in dopedZnO are high but, particularly for Mn doping, the reported moments have been small. We show that by careful control of both oxygen deficiency and aluminium doping the ferromagnetic moments measured at room temperature in n-type ZnMnO and ZnCoO are close to the ideal values of 5µ B and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
84
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(90 citation statements)
references
References 25 publications
4
84
2
Order By: Relevance
“…In samples that are dominated by n-type Zn interstitials and oxygen vacancies the magnetization decreases sharply as oxygen is added. 4 In contrast, in the films grown from Co metal precursors that have Zn vacancies, we found the largest RT magnetization in films grown at the highest pressure, which also had the largest grain sizes. The results indicate that the use of Co-metal as the precursor for the target is beneficial for the growth of films that do not contain metallic Co but are strongly magnetic.…”
contrasting
confidence: 61%
See 2 more Smart Citations
“…In samples that are dominated by n-type Zn interstitials and oxygen vacancies the magnetization decreases sharply as oxygen is added. 4 In contrast, in the films grown from Co metal precursors that have Zn vacancies, we found the largest RT magnetization in films grown at the highest pressure, which also had the largest grain sizes. The results indicate that the use of Co-metal as the precursor for the target is beneficial for the growth of films that do not contain metallic Co but are strongly magnetic.…”
contrasting
confidence: 61%
“…These include the stoichiometric transfer of material from the target to the film and the control of oxygenation during the film growth. A general trend for Co-doped ZnO has been to find that a deficiency of oxygen in the growth chamber enhances the ferromagnetism through the formation of donor states [4][5][6][7] and that annealing films in air or oxygen quenches any magnetization [8][9][10] although there are also a few conflicting results in which magnetism is observed in ZnO oxygenated films with and without doping with Co. 11,12 The role of metallic Co precipitates is less clear, with some authors claiming that they are responsible for all of the observed magnetic properties [13][14][15] ; however, other authors have identified ferromagnetic phases in ZnCoO films that lack any metallic component. 16,17 The PLD growth of ZnCoO starts from a target that has been made to the desired composition by a solid-state reaction of a Co-containing compound and zinc oxide.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the CTF model predicts that the moments are entirely localized on itinerant carriers confined to small regions possibly grain boundaries. 16 Although each model has its merits in certain aspects, [17][18][19][20][21][22][23][24][25][26] a complete understanding of the ferromagnetic behavior in oxide DMSs still calls for more microscopic insights into the defect structure, transport property, and moment distribution in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, the density of Zn vacancy is sensitive to experimental conditions and difficult to be controlled. Transition metal (TM) doping is a traditional method to obtain room temperature ferromagnetism in ZnO system [4,5,6,7,8,9,10,11,12]. However, the inconsistent experimental results raise a new problem of explaining the mechanism of ferromagnetism in TM-doped ZnO.…”
mentioning
confidence: 99%